ECB independence and accountability today: Towards a (necessary) redefinition? - Diane Fromage; Paul Dermine; Phedon Nicolaides; Klaus Tuori (Sage Publications Ltd., 2022)
This introductory article sets the ground for the analysis performed in the articles included in this Special Issue. It shows why a new analysis of the European Central Bank (ECB)’s accountability is required by referring to recent developments, and by underlining how much the ECB’s role and standing have changed since its creation 20 years ago. Indeed, its resorting to unconventional monetary policies in response to the recent economic and financial crisis, as well as the creation of the Banking Union, have significantly affected the ECB. This introduction also recalls the main elements of the debate on the balance between accountability and independence, and shows how this balance has evolved. On the basis of the findings of the articles included in this Special Issue, some conclusions and hypotheses as to the way forward are formulated.